Exploring patterns of Facebook usage, social capital, loneliness and well-being among a diverse South African student sample - Charles Young; Larry Strelitz (Communicare)
There has been much debate over whether the use of social network sites (SNSs) isolates people and truncates their relationships or, alternatively, provides beneficial connections with others. This debate has been framed by a growing body of international literature that explores the triadic relationship between the intensity of use of SNSs, the maintenance of social capital and the relationship between social capital and well-being/life satisfaction. Our exploratory research findings among students at Rhodes University, a small South African higher education institution, indicate that the historically shaped race and class cleavages impact on how this triadic relationship plays out.